A high eosinophil proportion increases the risk of skin-related adverse events induced by apalutamide in patients with prostate cancer - Tasaki, Yoshihiko; Naiki, Taku; Mimura, Yoshihisa; Sugiyama, Yosuke; Tomita, Misato; Morikawa, Toshiharu; Nagai, Takashi; Unno, Rei; Etani, Toshiki; Hamamoto, Shuzo; Umemoto, Yukihiro; Yasui, Takahiro; et al. (Frontiers in Immunology, 2025)
BackgroundSkin-related adverse events (AEs) induced by apalutamide occur frequently in Japanese patients with prostate cancer. However, biomarkers for predicting these skin-related AEs have not yet been identified. Therefore, this study investigated whether the proportion of eosinophils could serve as a predictive biomarker for skin-related AEs in Japanese patients with prostate cancer treated with apalutamide.MethodsA total of 109 patients were enrolled in this study. Among them, 79 patients with prostate cancer who received apalutamide were categorized into two groups: the skin AE group (n = 45) and the non-skin AE group (n = 34), based on whether they experienced skin-related AEs of any grade. The eosinophil proportions in baseline samples collected before treatment were then analyzed.ResultsThe baseline eosinophil proportion was significantly higher in the skin AE group compared with the non-skin AE group (P < 0.05). The optimal cut-off value of the eosinophil proportion for predicting skin-related AEs of any grade was 1.8% (area under the receiver operating characteristic curve [AUC] = 0.768). In multivariate analysis, an eosinophil proportion ≥1.8% was identified as an independent factor associated with skin-related AEs of any grade (odds ratio, 13.3; 95% confidence interval, 3.82–46.4; P < 0.05).ConclusionThe baseline eosinophil proportion may serve as a predictive biomarker for skin-related AEs of any grade in Japanese patients with prostate cancer treated with apalutamide.